2022
DOI: 10.1002/ctm2.759
|View full text |Cite
|
Sign up to set email alerts
|

Activation of autophagy reverses progressive and deleterious protein aggregation in PRPF31 patient‐induced pluripotent stem cell‐derived retinal pigment epithelium cells

Abstract: Introduction Mutations in pre‐mRNA processing factor 31 (PRPF31), a core protein of the spliceosomal tri‐snRNP complex, cause autosomal‐dominant retinitis pigmentosa (adRP). It has remained an enigma why mutations in ubiquitously expressed tri‐snRNP proteins result in retina‐specific disorders, and so far, the underlying mechanism of splicing factors‐related RP is poorly understood. Methods We used the induced pluripotent stem cell (iPSC) technology to generate retinal organoids and RPE models from four patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…To gain a better understanding, our group evaluated the activity of autophagy and the proteasome degradation system using multiple assays. Strikingly, our findings indicated that these waste disposal mechanisms are impaired, and hence cytoplasmic aggregates accumulate over time 1 . Similar observations were reported in other neurodegenerative diseases, where cytoplasmic accumulation of misfolded proteins have been associated with reduced or blocked activity of the waste disposal mechanisms 16,17 .…”
supporting
confidence: 86%
See 2 more Smart Citations
“…To gain a better understanding, our group evaluated the activity of autophagy and the proteasome degradation system using multiple assays. Strikingly, our findings indicated that these waste disposal mechanisms are impaired, and hence cytoplasmic aggregates accumulate over time 1 . Similar observations were reported in other neurodegenerative diseases, where cytoplasmic accumulation of misfolded proteins have been associated with reduced or blocked activity of the waste disposal mechanisms 16,17 .…”
supporting
confidence: 86%
“…AAV, aggregate formation, gene therapy, iPSC-RPE, PRPF31, retinal organoids, retinitis pigmentosa, RPE A recent publication by our group in Clinical and Translational Medicine titled 'Activation of autophagy reverses progressive and deleterious protein aggregation in in pre-mRNA (Messenger RNA) processing factors 31 (PRPF31) patient iPSC-derived retinal pigment epithelium (RPE) cells' provides new insights into why mutations in PRPFs cause retinitis pigmentosa (RP). 1 RP is an inherited retinal disease that affects more than 1 million individuals globally. 2 Approximately 15% of autosomal-dominant RP (adRP) cases are linked to genetic mutations in PRPFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a decreased degree of polarity, phagocytic ability and barrier function was observed in the RP-iRPE group compared to the NC-iRPE group. Such an aberrant phenotype was also observed in iPSC-RPE cells with PRPF31 mutation [ 38 , 39 ]. Their results also revealed that splicing defects appeared to be correlated with the ultrastructural, cellular and functional deficiencies that are characteristic of RPE in the RP disease state [ 38 ].…”
Section: Discussionmentioning
confidence: 81%
“…They observed that HDR-based CRISPR-correction resulted in the rescue of molecular and cellular phenotypes. The same iPSC lines were further characterized by Georgiou and colleagues, who showed localization of mutant PRPF31 in cytoplasmic aggregates in RP11 iPSC-RPE cells, in contrast to control cells where PRPF31 was localized in nuclear speckles required for splicing activity [ 103 ]. The authors also demonstrated that the dysregulation of splicing promoted protein misfolding and contributed to aggregate formation.…”
Section: Crispr-mediated Ipsc Editing For Inherited Retinal Disordersmentioning
confidence: 99%